Profile of Solriamfetol in the Management of Excessive Daytime Sleepiness Associated with Narcolepsy or Obstructive Sleep Apnea: Focus on Patient Selection and Perspectives - Abad VC (Dove Medical Press, 2021)
Vivien C Abad Department of Psychiatry & Behavioral Sciences, Division of Sleep Medicine, Stanford University, Redwood City, CA 94063, USACorrespondence: Vivien C AbadDepartment of Psychiatry & Behavioral Sciences Division of Sleep Medicine, Stanford University Outpatient Center, 450 Broadway St. Pavilion C.2nd Floor MC5704, Redwood City, CA 94063, USATel +1 650 723 6601Fax +1 650 721 3448Email vivien.abad@stanford.eduAbstract: Excessive sleepiness (ES) is a symptom of obstructive sleep apnea (OSA) and narcolepsy that has severe consequences. Wake-promoting drugs and stimulants are utilized as accessory treatment in OSA to reduce propensity to sleep but they do not improve sleep-disordered breathing. Solriamfetol is a first-line therapeutic agent to combat sleepiness in OSA and narcolepsy patients that is approved both by the Food and Drug Administration (FDA) and the European Medicines Agency (EMA). For excessively sleepy adult patients with OSA despite primary treatment or narcolepsy patients without cataplexy, solriamfetol may be used as initial therapy or as replacement therapy in patients who fail treatment or experience unacceptable side effects with modafinil, armodafinil, pitolisant, or stimulants. It can also be used as add-on therapy in OSA or narcolepsy patients when ES is only partially controlled with modafinil, armodafinil, pitolisant, sodium oxybate, or stimulants. Solriamfetol is a phenylalanine derivative whose wake-promoting action may be mediated through its selective dopamine and norepinephrine reuptake inhibition. This paper reviews the profile of solriamfetol in treating ES associated with OSA or narcolepsy and discusses patient selection and clinical perspectives. Mechanism of action, pharmacology, pharmacokinetics, clinical efficacy, and tolerability of solriamfetol are described. The Treatment of OSA and Narcolepsy Excessive Sleepiness (TONES) solriamfetol trials demonstrated the efficacy of solriamfetol in reducing propensity to sleep and maintaining wakefulness, with significant improvements in mean maintenance of wakefulness test (MWT) sleep latencies and significant reduction in Epworth Sleepiness Scale (ESS) scores compared to placebo. With solriamfetol, significantly higher percentages of patients showed improvement in patient’s and clinician’s global impression of change.Keywords: excessive daytime sleepiness, obstructive sleep apnea, narcolepsy, solriamfetol, drug profile, clinical perspective